Whatsapp based education in pandemic COVID-19 situation: Evaluating video and handbook's effect on knowledge of village community health-volunteers - Puspita Mardika Sari (BKM Public Health and Community Medicine, 2021)
Objective : Scope of iron supplementation in area of Puskesmas Mlati 2 have been reach targeted of RENSTRA of Sleman distric 2020. However, cases of anemia in pregnant woman still become a serious problem in this area. Based on “Root Caused Analysis” method, it was suggested that this problem was due to lack of knowledge about anemia and lack of precise instruction in consumption of iron suplement in pregnant woman. Therefore, program to increase knowledge about anemia and instruction of iron suplement consumption for pregnant woman was needed. However, in covid-19 pandemic situation, limitation of information accessed mainly in offline program become one of problem in community. Therefore, online program was needed. One of platform that can be used to organized these education was by using whatsapp group. It aslso completed with video and online handbook as media of education. Content : This article was report study of education program with video and online handbook media by using whatsapp group platform. This activity was implemented on 10 persons of community health-volunteers in Tlogoadi village as pilot project. Event was implemented on 2021, 8th June. Whatsapp group was named “Tlogoadi Cegah Stunting”. Program was evaluated by using pre test and post test method. Result was found that there were increasing of knowledge about anemia and precise instruction of iron supplement consumption on community health-volunteers after participated on this program. Conclusion: Education program by using whatsapp group platform, with video and online handboook were recommended as solution of education program in covid-19 pandemic situation. For the next target, community health-volunteers were recomended to convey the information as well as video and online handbook from this education program to public community in their area mainly to pregnant woman. This program also recommended to be implemented to other village of Puskesmas Mlati 2 area during covid-19 pandemic situation.